PENGARUH JUMLAH KUNJUNGAN WISATAWAN, PMDN, DAN JUMLAH PENDUDUK YANG BEKERJA TERHADAP PERTUMBUHAN EKONOMI PROVINSI BALI - Dewi, Dewa Ayu Kusuma; Bendesa, I Komang Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Economic growth is an important indicator to see the success of a country's economy. The Bali tourism sector is a sector that has the potential to be developed as a source of local revenue and economic growth. High investment, rapidly developing tourism sector, and high employment absorption can trigger high economic growth in an area. The purpose of this study was to determine the effect of the number of tourist visits, PMDN, and the number of working residents on economic growth in districts/cities in the province of Bali in 2015-2020. The data used in this research is secondary data. The analytical technique used is panel data regression analysis with the E-views 9 program. Based on the analysis, the results show that the number of tourist visits, PMDN, and the number of working residents simultaneously have a significant effect on Economic Growth in Regencies/Cities in Bali Province in 2015-2020. Partially, the number of tourist visits has a positive and significant effect, PMDN has no significant effect, and the number of working residents has a negative and significant effect on economic growth in districts/cities in Bali Province in 2015-2020 .